Transcriptome of Gonads From High Temperature Induced Sex Reversal During Sex Determination and Differentiation in Chinese Tongue Sole, Cynoglossus semilaevis - Wang, Qian; Liu, Kaiqiang; Feng, Bo; Zhang, Zhihua; Wang, Renkai; Tang, Lili; Li, Wensheng; Li, Qiye; Piferrer, Francesc; Shao, Changwei (Frontiers in Genetics, 2019)
Sex determination mechanisms in vertebrates can be broadly divided into genetic sex determination (GSD) and environmental sex determination (ESD). In addition, some fish species display plasticity during sex determination so that environmental factors can also alter the primary sex to the opposite direction without changing the genotype, a phenomenon called environmental sex reversal (ESR). Temperature is the main factor and thus elevated temperature can have a masculinizing effect. Previous studies on temperature-related ESR have been restricted to genes differentially expressed in mature gonads, or lacking a sex reversed pseudomale description. Thus, the molecular mechanism governing ESR remains a mystery in fish. The Chinese tongue sole (Cynoglossus semilaevis) is a perfect suitable model to illuminate the relationship of sex-determination and temperature because the co-existence of GSD (genetic sex determination) and ESD (environmental sex determination). In the present study, undifferentiated gonads from genetic females and males, plus differentiated gonads from males, females, and pseudomales under high temperature and normal temperature treatment were used for comparative transcriptome analysis. A mean of 68.24 M high-quality clean reads were obtained from each library. The differentially expressed genes (DEGs) related to sex and environmental temperature identified that the heat shock protein gene family had an important role in sex reversal induced by high temperature. Enrichment analyses of GO terms and KEGG pathways showed that Neuroactive ligand-receptor interaction, Cortisol synthesis and secretion, and Steroid hormone biosynthesis may be involved in high temperature induced pseudomale formation. Furthermore, via weighted gene co-expression network analyses, two modules were identified to be significantly positive correlated with pseudomale under high temperature. An illustrated protein-protein interaction map drawn by the yellow module identified a hub gene, hsc70. These findings provide insights into the genetic framework underlying sex determination and sexual differentiation, as well as improve our understanding of the underlying ESR mechanism of sex reversal under high temperature.